A mechanistic overview of approaches for the treatment of psychostimulant dependence - Kathrine Louise Jensen; Søren Brøgger Jensen; Kenneth Lindegaard Madsen (Frontiers Media S.A., 2022)
Psychostimulant use disorder is a major health issue around the world with enormous individual, family-related and societal consequences, yet there are no effective pharmacological treatments available. In this review, a target-based overview of pharmacological treatments toward psychostimulant addiction will be presented. We will go through therapeutic approaches targeting different aspects of psychostimulant addiction with focus on three major areas; 1) drugs targeting signalling, and metabolism of the dopamine system, 2) drugs targeting either AMPA receptors or metabotropic glutamate receptors of the glutamate system and 3) drugs targeting the severe side-effects of quitting long-term psychostimulant use. For each of these major modes of intervention, findings from pre-clinical studies in rodents to clinical trials in humans will be listed, and future perspectives of the different treatment strategies as well as their potential side-effects will be discussed. Pharmaceuticals modulating the dopamine system, such as antipsychotics, DAT-inhibitors, and disulfiram, have shown some promising results. Cognitive enhancers have been found to increase aspects of behavioural control, and drugs targeting the glutamate system such as modulators of metabotropic glutamate receptors and AMPA receptors have provided interesting changes in relapse behaviour. Furthermore, CRF-antagonists directed toward alleviating the symptoms of the withdrawal stage have been examined with interesting resulting changes in behaviour. There are promising results investigating therapeutics for psychostimulant addiction, but further preclinical work and additional human studies with a more stratified patient selection are needed to prove sufficient evidence of efficacy and tolerability.